Hotspots and Frontiers in Inflammatory Tumor Microenvironment Research: A Scientometric and Visualization Analysis - Zhang, Yuli; Huo, Long; Wei, Zhenzhen; Tang, Qingfeng; Sui, Hua (Frontiers in Pharmacology, 2022)
Background: Inflammatory tumor microenvironment is an essential feature of tumor microenvironment. The way in which it promotes or inhibits tumor progression plays an important role in the outcome of tumor treatment. This research aims to explore a scientific collaboration network, describe evolution of hotspots, and predict future trends through bibliometric analysis. Methods: Articles on inflammatory tumor microenvironment were retrieved from Web of Science Core Collection and characteristics of the articles were analyzed by CiteSpace software. Results: A total of 3534 papers published by 390 institutions in 81 countries/regions were screened and the annual quantity has been increasing rapidly in the past decades. USA was the leading country and have the most productive institutions in this field. The research topics were mainly focused on inflammation and immunity mediated by crucial factors, as well as the mechanisms of angiogenesis. Additionally, the development and application of nanoparticles is currently a novel research frontier with bright prospect. Conclusion: The present scientometric study provides an overview of the inflammatory tumor microenvironment research over the previous decades using quantitative and qualitative methods, and the findings of this study can provide references for researchers focusing on tumor treatment.